Study of correlation between fetomaternal outcome with placental location at a tertiary hospital - Sitimani, Anita; Sai, Balumuri Pooja; S., Bandamma Narendra; Prabhudev, Prema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The site of implantation and location of placenta can affect the blood supply of placenta which is likely important determinant of placental blood flow and pregnancy outcome. Methods: In our study 240 pregnant women of 19-35 years, singleton ≥28 weeks underwent ultrasound examination for placental localization. Results: Majority of pregnant women were from 21-25 years age, multigravida and placental location in majority was lateral. Adverse events were PROM, preeclampsia/ eclampsia, IUGR, preterm birth was noted with lateral location of placenta. Conclusions: A significant association was noted between lateral placentation of placenta and adverse fetomaternal outcome. Ultrasound examination can be used as non-invasive predictor of adverse pregnancy and neonatal outcomes.